Biodegradação de filmes de polietileno de baixa densidade (PEBD), polihidroxibutirato-co-hidroxivalerato (PHBV) e blenda de PEBD/PHBV (70/30), em coluna de solo - Bucioli, Elaine Cristina [UNESP] (2014)
Plastics are materials with large-scale industrial application and economic importance to modern society. The use of synthetic plastics in packaging and disposable products generates socio- environmental due to improper disposal and disposal of this material impacts . One alternative to minimize these effects is the production of blends which have their own characteristics and use after use, to be absorbed in a short period of time in the environment . This study evaluated the biodegradation of PHBV films (poly ( hydroxybutyrate-co- hydroxyvalerate ) ) , films of LDPE ( low density polyethylene ) and LDPE blend / PHBV ( 70/30 ) in the soil column using methodologies as: Scanning Electron Microscopy (SEM ) , Fourier Transform Infrared ( FTIR ) and weight loss evaluation. PHBV was biodegraded within 30 days of exposure to the soil , the less exposure time compared to LDPE and blends in 180 days . Through SEM we observed significant micro morphological changes on the surface of PHBV and blend films ( holes , fractures , desquamation and erosions ) , which complements the values found of mass loss , where the PHBV decreased by 43.9 % and the blend showed a reduction of 15.7% in the respective periods of the biodegradation process. The FTIR spectra provide important information for assessing biodegradation because they showed the important structural changes after the biodegradation process , such as hydrolysis of esters of PHBV at the interface between LDPE and PHBV . Using FTIR analysis was verified crystallinity change of the polymer materials, which was an indication of the films biodegradation. The blend in this ratio, shown to be susceptible to the soil microbial community, undergoing significant changes in its morphology